2013
DOI: 10.1016/j.bbamem.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Selective antimicrobial activity and mode of action of adepantins, glycine-rich peptide antibiotics based on anuran antimicrobial peptide sequences

Abstract: A challenge when designing membrane-active peptide antibiotics with therapeutic potential is how to ensure a useful antibacterial activity whilst avoiding unacceptable cytotoxicity for host cells. Understanding their mode of interaction with membranes and the reasons underlying their ability to distinguish between bacterial and eukaryotic cytoplasmic cells is crucial for any rational attempt to improve this selectivity. We have approached this problem by analysing natural helical antimicrobial peptides of anur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…The selectivity index is used routinely to describe the selectivity of the compound towards a particular bacterium. 37,38 This is obtained by dividing the haemolysis concentration 50 (HC 50 ) value by the MIC value for a given bacterium: these values are shown in Table SI 7.…”
Section: Resultsmentioning
confidence: 99%
“…The selectivity index is used routinely to describe the selectivity of the compound towards a particular bacterium. 37,38 This is obtained by dividing the haemolysis concentration 50 (HC 50 ) value by the MIC value for a given bacterium: these values are shown in Table SI 7.…”
Section: Resultsmentioning
confidence: 99%
“…The most hydrophobic peptides are LVHYAGTVDYN and FRPQQPYPQP. Extensive examination of identified peptides in sub-fraction B, revealed that NVLSGGTTMYPG, FRPQQPYPQP, GPRGLPGSPGNIGPAG, and VRNDNSSRFGKF are glycine and/or proline and/or arginine rich peptides, a common characteristic of several AMPs reported in literature (Ilic' et al, 2013;Otvos, 2002;Dong et al, 2012).…”
Section: Fractionation and Identification Of Bioactive Peptidesmentioning
confidence: 99%
“…To mimic the mammalian membrane 1,2-dimyristoyl-sn-glycerophosphocholine (DMPC) was chosen as it is widely used. 22,23 To mimic the bacterial membrane, a mixture of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoglycerol (POPG) at 1:1 molar ratio was chosen as it has been described as one of the most biologically relevant model membranes for studying the S. aureus strain. 24 ■ EXPERIMENTAL SECTION Reagents.…”
Section: ■ Introductionmentioning
confidence: 99%